Jack Irish : [videorecording (DVD)] the movies - Temple, Peter, 1946-2018; Pearce, Guy, 1967-; Dusseldorp, Marta, 1973-; Pedersen, Aaron, 1970- (Acorn Media, 2012)
Jack Irish, is a brooding antihero of Australia. Reeling in the wake of his wife's murder, the former lawyer has reinvented himself as a part-time private investigator and full-time alcoholic, intent on drowning his demons. When an old client dies after leaving Jack several frantic voicemails, the PI realizes he can't outrun or out-drink his past. Jack returns to the world that took everything away from him: a seedy place of lowlifes, corruption, violence, and retribution.